2023
DOI: 10.1177/00343552231155218
|View full text |Cite
|
Sign up to set email alerts
|

Use of Research-Based Transition Recommendations for Youth With Disabilities in Workforce Innovation and Opportunity Act Plans

Abstract: As vocational rehabilitation (VR) agencies continue to implement provisions of the Workforce Innovation and Opportunity Act (WIOA) to provide employment-related transition services to youth with disabilities, it is unclear if implementation plans include predictors of post-school employment and evidence-based transition practices. We conducted a content analysis of 54 state/territory VR agency WIOA plans from 2020 to determine the extent to which research-based transition recommendations (RBTRs) were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…As we enter the second decade of WIOA interpretation and implementation, we are optimistic about state VR agencies' capacity to address known barriers to delivering Pre-ETS (e.g., Awsumb et al, 2020;Carter et al, 2021;Poppen et al, 2021;Taylor et al, 2022;Whittenburg et al, 2023). The findings we have presented lead to a set of recommendations that VR agencies can work to further address.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As we enter the second decade of WIOA interpretation and implementation, we are optimistic about state VR agencies' capacity to address known barriers to delivering Pre-ETS (e.g., Awsumb et al, 2020;Carter et al, 2021;Poppen et al, 2021;Taylor et al, 2022;Whittenburg et al, 2023). The findings we have presented lead to a set of recommendations that VR agencies can work to further address.…”
Section: Discussionmentioning
confidence: 89%
“…Yet, these barriers persist and are compounded by imperfect communication between VR and state education agencies (SEAs) and LEAs, and limited time and resources (e.g., Carter et al, 2021;Lambert et al, 2023;Zhang et al, 2023). Furthermore, VR agencies have continued to struggle with translating policy into practice to meet WIOA requirements (e.g., GAO, 2018;Taylor et al, 2022;Whittenburg et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…As we consider these factors, research has shown that states have varied widely in how they have prioritized WIOA implementation in general (Taylor et al, 2022), Pre-ETS delivery in particular (Whittenburg et al, 2024), and the degree to which they have incorporated research-based practices in Pre-ETS planning (Whittenburg et al, 2023). Additionally, there is significant variation in who provides Pre-ETS within states, with some states providing all services through VR staff, others providing all services through vendor-purchased service agreements, and the majority through a combination of the two (Whittenburg et al, 2024).…”
Section: The Challengementioning
confidence: 99%
“…Likewise, most states identified community-based experiences as the primary context for Pre-ETS delivery but differed greatly in the amount of time and intensity to be devoted to such experiences (Taylor et al, 2022). Additionally, Whittenburg et al (2023) found that states also varied widely in the degree to which they incorporated research-based transition recommendations in their planning and delivery of Pre-ETS. The findings from Carlson (2020), Taylor et al (2022), andWhittenburg et al (2023) show that a student's experience with Pre-ETS is likely to differ simply as a matter of their respective state of residence.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Whittenburg et al (2023) found that states also varied widely in the degree to which they incorporated research-based transition recommendations in their planning and delivery of Pre-ETS. The findings from Carlson (2020), Taylor et al (2022), andWhittenburg et al (2023) show that a student's experience with Pre-ETS is likely to differ simply as a matter of their respective state of residence.…”
Section: Introductionmentioning
confidence: 99%